Study on the Effect of Jet Position and Size on Heat Transfer in a Small Containment - Xiong, Wang; Fang, Yuan; Lin, Shengsheng; Wang, Shengfei (Frontiers in Energy Research, 2022)
In the main steam line break (MSLB) accident, the rise in temperature and pressure threatens the integrity of the containment, which is caused by a large amount of mixed gas injected into the containment rapidly. Due to the structural difference between small and large containment, it is necessary to study the heat transfer in the complex space of the small containment. Based on the research method, which is from simple to complex, in this study, a series of experiments and numerical simulations are carried out with different jet positions and sizes using hot air without phase change as the working medium. The results show that the temperature field above the jet is complex and affected by many factors such as buoyancy, initial kinetic energy, and internal structure. When the jet flow rate is constant, the jet size is smaller and the velocity is faster, which results in a large circulation and stronger heat exchange with the wall of containment. This means that the temperature above the jet is lower than the large jet size, and the temperature below the jet is slightly higher. The jet position mainly affects the relative position of the jet and the complex space in the containment. When the jet is located in a narrow space, the overall temperature in the containment is higher than the jet located in a large space. In addition, when it is close to the obstacle, the core region of the jet will shift slightly toward the obstacle.